2013
DOI: 10.1039/c2ce26814k
|View full text |Cite
|
Sign up to set email alerts
|

Calcium sulfate hemihydrate-mediated crystallization of gypsum on Ca2+-activated cellulose thin films

Abstract: Spin-coated cellulose thin films have been used as model substrates to investigate the crystallization of calcium sulfate dihydrate (gypsum) under industrially relevant conditions using highly concentrated dispersions of calcium sulfate hemihydrate (bassanite). Pre-treatment of the films by regeneration in aqueous solutions of Ca 2+ promotes gypsum crystallization specifically on the polysaccharide substrate in the presence of bassanite or in control solutions comprising supersaturated calcium sulphate. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…3 Usually, bassanite is obtained by heating of gypsum at temperatures between 100 and 150°C in dry state [4][5][6] or at 75°C in methanol-water solutions, 7 leading to partial release of hydration water. Upon subsequent addition of water, it transforms back into gypsum in a rapid exothermic hydration process, 2,8,9 which accounts for the setting and hardening of plaster and cement materials.…”
mentioning
confidence: 99%
“…3 Usually, bassanite is obtained by heating of gypsum at temperatures between 100 and 150°C in dry state [4][5][6] or at 75°C in methanol-water solutions, 7 leading to partial release of hydration water. Upon subsequent addition of water, it transforms back into gypsum in a rapid exothermic hydration process, 2,8,9 which accounts for the setting and hardening of plaster and cement materials.…”
mentioning
confidence: 99%
“…They pretreated the cellulose thin films with Ca 2+ ions and exposed the films to concentrated solutions of Bassanite (calcium sulfate hemihydrate). They observed that depending on the activation procedure the rate of crystallization can be controlled (Nissinen et al, 2013, 2014). In a recent report, cellulose thin films were decorated with different nanodots [silicon-dots (SiDs), carbon-dots (CDs)] or nitrogen-doped carbon dots (N-CDs).…”
Section: Materials Applications Of Ultrathin Cellulose Filmsmentioning
confidence: 99%
“…This study aims to investigate the use of commercially available gypsum for treating synthetic wastewater. Gypsum is an inorganic substance which has a high affinity to metal ions that led scientist to investigate the potential use of this environmentally friendly compound to remove toxic metal ions from wastewater (Rauf et al 2009;Gou and Lua 2003;Mall et al 2007;Ayrancci and Duman 2005;Yan et al 2014;Mittal et al 2008;Deniz and Saygideger 2010;Yagub et al 2014;Nissinen et al 2013). Naturally, GS particles possess positive charges (Raii et al 2012).…”
Section: Introductionmentioning
confidence: 99%